2015
DOI: 10.3168/jds.2014-8923
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Prevalence of Staphylococcus aureus and methicillin-resistant S. aureus in bulk tank milk from dairy goat farms in Northern Italy

Abstract: Staphylococcus aureus is regarded as a leading cause of mastitis in goats. However, few data are available on the presence of methicillin-resistant S. aureus (MRSA) in this species. The aim of this study was to assess the prevalence of S. aureus and MRSA in bulk tank milk samples from dairy goat farms in Northern Italy. Eighty-five out of 197 samples (43.1%) tested positive for S. aureus with counts ranging from 10 to more than 1.5 × 10(4) cfu/mL. The MRSA was screened by both direct plating followed by a disk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 26 publications
(38 reference statements)
6
51
0
1
Order By: Relevance
“…Similar to our results, S. aureus was detected in 24% of the raw OM samples collected from Epirus, Greece (Fotou et al 2011), whereas all milk samples collected from 21 sheep farms from the regions of Xanthi and Evros were positive for S. aureus . The data regarding the prevalence of S. aureus in CM and OM from other countries are also quite variable (Mørk et al 2003;Jørgensen et al 2005;de Garnica et al 2013;Spanu et al 2013;Cortimiglia et al 2015). Although differences in the sensitivity and specificity of the protocols used for bacterial isolation may have contributed to these variant results, the different husbandry practices applied in different countries may at least partly account for the aforementioned differences in prevalence estimates.…”
Section: Antibiotic Susceptibility Of S Aureus Isolatesmentioning
confidence: 88%
See 2 more Smart Citations
“…Similar to our results, S. aureus was detected in 24% of the raw OM samples collected from Epirus, Greece (Fotou et al 2011), whereas all milk samples collected from 21 sheep farms from the regions of Xanthi and Evros were positive for S. aureus . The data regarding the prevalence of S. aureus in CM and OM from other countries are also quite variable (Mørk et al 2003;Jørgensen et al 2005;de Garnica et al 2013;Spanu et al 2013;Cortimiglia et al 2015). Although differences in the sensitivity and specificity of the protocols used for bacterial isolation may have contributed to these variant results, the different husbandry practices applied in different countries may at least partly account for the aforementioned differences in prevalence estimates.…”
Section: Antibiotic Susceptibility Of S Aureus Isolatesmentioning
confidence: 88%
“…In our study, the MRSA isolate was resistant to AK, NN, FOX, DA, and E. Cortimiglia et al (2015) reported that three out of four MRSA isolates from bulk CM were resistant to TE, besides being resistant to penicillin and FOX. In addition, two of them were resistant to trimethoprim and one to DA.…”
Section: Antibiotic Susceptibility Of S Aureus Isolatesmentioning
confidence: 94%
See 1 more Smart Citation
“…In Italy, the community-acquired MRSA (CA-MRSA) ST(CC) 1 spa -type t127 is reported among the main lineages of MRSA isolated in livestock productions [15,16,17,18,19,20,21]. CA-MRSA clones often harbor the PVL virulence genes, more than CA-MSSA, suggesting that methicillin resistance has contributed to the success of pvl -positive S. aureus strains [22].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent isolates are S. aureus, in clinical cases, and coagulasenegative species (CNS), in subclinical cases of intramammary infection (IMI) (BERGONIER et al, 2003). Control measures for S. aureus mastitis are important in order to reduce economic losses and decrease the risk of diseases, being transmitted to humans via food (CORTIMIGLIA et al, 2015). For instance, these authors recorded a high prevalence of S. aureus in herds of dairy goats by isolating methicillin-resistant strains (MRSA).…”
Section: Introductionmentioning
confidence: 99%